Gestión de los procesos de distribución y ventas de la distribuidora Jehová Shalom, de Riobamba, provincia de Chimborazo, período 2023 - Llamuca Centeno, Gennesis Belen (2025)
In distribution and marketing companies, the stages of the distribution process (warehousing, invoicing, distribution, and collection) play a key role in achieving good profitability. When these stages are managed efficiently, costs are reduced, inventory control is improved, and timely customer service is facilitated, contributing to the company's revenues. This research aimed to analyze the distribution and sales processes of the Jehovah Shalom Distributor in the city of Riobamba, province of Chimborazo, period 2023. A non- experimental design was used, with a mixed approach and descriptive level, applying the analytical method. The population consisted of 8 workers of the company, in addition to a documentary population. A survey was used as a data collection technique, consisting of eight questions identifying the factors that influence the distribution process. Among the main results, it was identified that the company does not adequately apply its distribution process, generating negative effects on its financial results. Through hypothesis testing, it was determined that the stages of the distribution process do not have a direct influence on the financial results of the distributor; however, through correlation analysis, it was found that there is a relationship between the distribution stage and the company's profitability.